DERMOELECTROPORATION IN THE TREATMENT OF OVERUSE INJURIES - S. Radev (Trakia Journal of Sciences)
The musculoskeletal system can suffer from various types of overuse injuries which may affect the bone, muscles, tendons and ligaments. Iliotibial band syndrome (ITBS) is a common overuse injury typically seen in runners, cyclist and other endurance athletes, whose sport requires repetitive knee flexion. The majority of cases resolve with conservative treatment. Care in the acute phase focuses on activity limitation, NSAIDʼs, corticosteroids. Analgesia and pain management are two very important aspects in the therapeutic process. The research project is focused on the dermoelectroporation (pulse current iontophoresis), as a new method for transdermal drug delivery. It was evaluated the feasibility administering the cocktail of Diclofenac Sodium and Dexamethasone Sodium Phosphate by dermoelectroporation (pulse current iontophoresis), for treatment of ITBS. Diclofenac Natrium and Dexamethasone Sodium Phosphate was given locally, via dermoelectroporation (pulse current iontophoresis) in the area of pain (area of the damaged lateral femoral condyle), following microdermabrasion. The therapeutic procedures were performed every day, once a day, 3 times. The pain threshold was recorded objective with Pressure Algometer Somedic in kPa/cm2. The subjective intensity of the painful sensation was assessed with 10 cm Visual Analogue Scale (VAS), ranging from 0 cm (no pain) to 10 cm (worst possible pain). Using this method of application of nonsteroidal and steroidal anti-inflammatory drugs has significant benefits like: quick pain relief, minimally invasive effect for the patient and minimum side effects. Based on these advantages it is thought that dermoelectroporation could be a preferable way of administering antiinflammatory drugs in inflammatory-degenerative conditions related to the musculoskeletal system, such as overuse injuries like tendinopathies.